Adubação nitrogenada para consórcio de alface e rúcula - Barboza, Eliza [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The viability of the intercropping of lettuce and rocket is scientifically proven, but there is a lack of study on fertilization of crops in this farming system, being used nutrient rates recommended for crops in sole. The objective of this study was to evaluate the effect of different Nitrogen (N) rates on yield of lettuce and rocket, in intercropping, to obtain the optimal rate that would maximize the intake of nitrogen by crops and thus increase yield. The experimental design was a randomized complete block design with four replications in a factorial arrangement 2 x 6 + 3. Two lettuce cultivars('Amanda' and 'Lucy Brown') were used in intercropping with rocket 'Folha Larga'. Six different rates of N (0, 120, 240, 360, 480 and 600 kg ha-1) were applied. And three additional, corresponding to monoculture lettuce crisp, american and rocket treatments. Leaf N content of lettuce and rocket, rocket height, shoot dry mass (SDM) and yield of lettuce and rocket and efficiency of use of the area (EUA) were evaluated. The leaf N content for 'Amanda' and 'Lucy Brown' increased up to 600 kg ha-1, but stood in the proper range for N lettuce with doses from 48 kg and 40 kg N ha-1, respectively. With 120, 75, 180 and 120 kg ha-1 N were obtained 94, 95, 84 and 92% of MSPA 'Amanda' and 'Lucy Brown', rocket with 'Amanda' and rocket with 'Lucy Brown', respectively. Largest increase in smaller doses provide MSPA than 0.1% for every 1 kg ha-1 of N added. Maximum yield of 'Amanda' and 'Lucy Brown' in intercropping with rocket were obtained with 290 and 243 kg ha-1 N, respectively, while for the rocket in association with 'Amanda' and 'Lucy Brown' took 600 kg ha-1 N. the total N exported by association 'Amanda' and 'Lucy Brown' with rocket, as the EUA indices were 41.6 and 27.71 kg ha-1 N respectively

A viabilidade do consórcio de alface e rúcula é comprovada cientificamente, porém há carência de estudo sobre a fertilização das culturas neste sistema de cultivo, sendo utilizadas as doses de nutrientes recomendadas para as culturas em cultivo solteiro. O objetivo deste trabalho foi avaliar o efeito de doses de N na produtividade da alface e rúcula, em consórcio, obter a dose que maximiza a eficiência de uso da área e verificar a exportação de nitrogênio pelas culturas. O delineamento experimental foi em blocos casualizados, com quatro repetições, arranjados em esquema fatorial 2 x 6 + 3. Os fatores avaliados foram duas cultivares de alface ('Amanda' e 'Lucy Brown') em consórcio com a rúcula 'Folha Larga' e seis doses de N aplicadas em plantio e cobertura: 0, 120, 240, 360, 480 e 600 kg ha-1. Os três tratamentos adicionais corresponderam às monoculturas das alfaces e rúcula. O teor foliar de N para 'Amanda' e 'Lucy Brown' aumentou até 600 kg ha-1, porém situaram-se na faixa adequada de N para alface com doses a partir de 48 e 40 kg ha-1 de N, respectivamente. Máximas produtividades de 'Amanda' e 'Lucy Brown' em consórcio com rúcula foram obtidas com 290 e 243 kg ha-1 de N, respectivamente, enquanto para maximizar a produtividade da rúcula em associação à 'Amanda' e 'Lucy Brown' foram necessários 260 e 124 kg ha-1 de N, respectivamente. Máximos índices de eficiência do uso da área (EUA) dos consórcios 'Amanda' e 'Folha Larga' e de 'Lucy Brown' e 'Folha larga' foram obtidos com 180 e 110 kg ha-1 de N. O total de N exportado pelos consórcios 'Amanda' e 'Lucy Brown' com rúcula, com os máximos índices EUA foram de 41,6 e 27,7 kg ha-1 de N, respectivamente
Keywords: Alface; Adubação; Fertilizantes nitrogenados; Cultivo consorciado; Nitrogenio na agricultura; Nitrogen in agriculture